2020
DOI: 10.15259/pcacd.25.015
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a New Generation of Chitosan Hydrogels Containing Pyrimidine Ribonucleotides

Abstract: Damage to the nervous system, in particular spinal cord injuries, is a burden for the patient and is usually the cause of irreversible disability. The progress observed in the last decade in the fields of biology, biomaterial engineering and neurosurgery has created new treatment solutions while preventing further neurodegenerative processes. The most important research is focused on the implementation of polymer structures in clinical practice, especially chitosan hydrogels, which are the scaffolds for regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The FTIR spectra of the lyophilized hydrogels obtained from the chitosan lactate solutions with UMP containing the addition of GO and, as a reference point, the spectrum of the unmodified system (the CH/LA/UMP system) are illustrated in Figure 5. Analyzing the above spectra, it can be noticed that the introduction of GO into the chitosan lactate solutions only contributed to differences in the intensity of the absorption signals identified for the control sample (the CH/LA/UMP system), discussed in detail in our publications [25][26][27]. This proves the good dispersion of the nanofiller into the polymer matrix.…”
Section: Structural Characteristics Of the Modified Chitosan Hydrogelsmentioning
confidence: 59%
“…The FTIR spectra of the lyophilized hydrogels obtained from the chitosan lactate solutions with UMP containing the addition of GO and, as a reference point, the spectrum of the unmodified system (the CH/LA/UMP system) are illustrated in Figure 5. Analyzing the above spectra, it can be noticed that the introduction of GO into the chitosan lactate solutions only contributed to differences in the intensity of the absorption signals identified for the control sample (the CH/LA/UMP system), discussed in detail in our publications [25][26][27]. This proves the good dispersion of the nanofiller into the polymer matrix.…”
Section: Structural Characteristics Of the Modified Chitosan Hydrogelsmentioning
confidence: 59%
“…The verification of the above proposals was created based on structural and rheological tests. Studies with the use of β-GP are presented in publications [ 33 , 34 , 35 , 50 , 51 ] and with the use of UMP in the articles [ 32 , 33 ]. On the other hand, Peters et al [ 52 ] demonstrated the molecular structure containing a ribose sugar with purines or pyrimidines that can be formed with intermolecular attractions, including π-π stacking, electrostatic interactions and hydrogen bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Systems obtained from chitosan lactate and chitosan chloride solutions with the use of β-glycerol phosphate disodium salt pentahydrate (β-GP) or uridine 5′-monophosphate disodium salt (UMP) [ 32 , 33 ] as the cross-linking agents were investigated. Rheological measurements were carried out to define the sol-gel transition point of the analyzed chitosan systems, and their outcomes were compared with the results of experiments performed with nuclear magnetic resonance (NMR).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that the combination of chitosan with organic-inorganic composites can significantly improve chitosan activity. A large increase in the compressive strength (more than 10-fold) and the maximum strain (more than 25-fold) was achieved for a blend with 10% chitosan content [184]. Silica has many valuable properties for polymers.…”
Section: Silicamentioning
confidence: 99%